TECHNICAL AND ECONOMIC ANALYSIS OF IRRIGATION, FERTIGATION AND PLASTIC COVER ON THE TABLE GRAPE 'ITÃLIA' IN THE SERRA GAÃšCHA, STATE OF RIO GRANDE DO SUL, BRAZIL - Monteiro, Rodrigo OtÃ¡vio CÃ¢mara; Monteiro, Priscylla Ferraz CÃ¢mara (REVISTA DE AGRICULTURA, 2013)
Recent drought periods in the Serra Gaúcha Region have triggered farmers´ interest in adopting irrigation (IS) and fertigation systems (FES).There is little technical information regarding irrigation features and management, high price variation, variety of irrigation equipment brands and their useful life, and there is little technical and economic irrigation data to assist farmers. The objective of the present study was to study the technical and economic feasibility of irrigation, fertigation and plastic cover for the table grape cultivar ‘Itália’ vineyards in the Serra Gaúcha region, considering climatic conditions and irrigation systems used. For technical and economic feasibility of IS and FES installation in the ‘Italy’ table grape vine yards under plastic cover in the Serra Gaúcha region there must be a productivity increase from 29% (IS low cost, long useful life and installed in the plant production stability phase) to 53.7% (FES automated, short useful life and installed in the first year of growing crop phase).